Local Resistance in Early Medieval Chinese Historiography and the Problem of Religious Overinterpretation. (October 2014) - Espesset, Grégoire
The official corpus of Chinese historiography contains a wealth of valuable information on what may be termed local resistance to the centralised empire in early medieval China (third to sixth century). Sinologists specialised in the study of Chinese religions commonly reconstruct the religious history of the era by interpreting some of these data. In the process, however, methodological mistakes often occur, such as disregard for the primary purpose of the historiography of local resistance, and 'overinterpretation'—that is, 'fabricating false intensity' and 'seeing intensity everywhere', as French historian Paul Veyne proposed to define the term. Focusing on a cluster of historical anecdotes collected in the standard histories of the four centuries under consideration, this study discusses how the supposedly 'religious' data therein should, and should not, be dealt with.